Beginning Scala programming : an introduction to methods, classes, functions, and collections - Hinojosa, Daniel (O'Reilly, 2016)
"In this Beginning Scala Programming training course, expert author Daniel Hinojosa will teach you everything you need to know about methods, classes, functions, and collections in Scala. This course is designed for the absolute beginner, meaning no previous experience with Scala is required. You will start by learning how to create a script and application in Scala, then jump into learning the Scala basics. From there, Daniel will teach you about Scala methods, Scala classes, and objects. This video tutorial also covers the apply method and higher order functions. Finally, you will learn about collection basics and collections with functions. Once you have completed this computer based training course, you will have learned everything you need to know to get started with Scala."--Resource description page.